Assessment of fish and invertebrate assemblages, and availability of food supporting fishery resources at Humacao Natural Reserve lagoon system, Puerto Rico - Ferrer, Orlando; Dibble, Eric; Jackson, Donald; Rundle, Kirk (Ciencia)
The Humacao Natural Reserve (HNR) lagoon system, Puerto Rico has become an important fish source for eastern Puerto Rico. Principal fishes targeted are tarpon (Megalops atlanticus), common snook (Centropomus undecimalis), swordspine snook (C. ensiferus), Mozambique tilapia (Orecochromis mossambicus) and redbreast tilapia (Tilapia rendalli). We asked whether the HNR lagoon system had a sufficient functional structure to support sustainable principal fish fisheries. To answer this question, we collected fish and invertebrates with light traps (N = 129), pop nets (N = 224), seines (N = 208), gill nets (N = 228), and trap nets (N = 123) and determined the physicochemical and habitat structure of the lagoon system between March 2000 and May 2001. Canonical correspondence analysis (CCA) indicated that there was a strong association between salinity and the fish assemblage along the linear series of lagoons from the Mandri through the Santa Teresa systems. The CCA also indicated that each principal fish species was associated with a different set of environmental variables; tarpon was associated with low salinity, dissolved oxygen, and temperature; snook were associated with high salinity, whereas tilapia were associated with high dissolved oxygen and temperature. All our analyses indicated that the HNR lagoon system was a fully functional system supporting sustainable fisheries.